Risk factors and the value of microbiological examinations of COVID-19 associated pulmonary aspergillosis in critically ill patients in intensive care unit: the appropriate microbiological examinations are crucial for the timely diagnosis of CAPA - Zhou, Xiaoyi; Wu, Xiaojing; Chen, Ziying; Cui, Xiaoyang; Cai, Ying; Liu, Youfang; Weng, Bingbing; Zhan, Qingyuan; Huang, Linna (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction During the Omicron pandemic in China, a significant proportion of patients with Coronavirus Disease 2019 (COVID-19) associated pulmonary aspergillosis (CAPA) necessitated admission to intensive care unit (ICU) and experienced a high mortality. To explore the clinical risk factors and the application/indication of microbiological examinations of CAPA in ICU for timely diagnosis are very important. Methods This prospective study included patients with COVID-19 admitted to ICU between December 1, 2022, and February 28, 2023. The clinical data of influenza-associated pulmonary aspergillosis (IAPA) patients from the past five consecutive influenza seasons (November 1, 2017, to March 31, 2022) were collected for comparison. The types of specimens and methods used for microbiological examinations were also recorded to explore the efficacy in early diagnosis. Results Among 123 COVID-19 patients, 36 (29.3%) were diagnosed with probable CAPA. CAPA patients were more immunosuppressed, in more serious condition, required more advanced respiratory support and had more other organ comorbidities. Solid organ transplantation, APACHEII score ≥20 points, 5 points ≤SOFA score <10 points were independent risk factors for CAPA. Qualified lower respiratory tract specimens were obtained from all patients, and 84/123 (68.3%) patients underwent bronchoscopy to obtain bronchoalveolar lavage fluid (BALF) specimens. All patients’ lower respiratory tract specimens underwent fungal smear and culture; 79/123 (64.2%) and 69/123 (56.1%) patients underwent BALF galactomannan (GM) and serum GM detection, respectively; metagenomic next-generation sequencing (mNGS) of the BALF was performed in 62/123 (50.4%) patients. BALF GM had the highest diagnostic sensitivity (84.9%), the area under the curve of the mNGS were the highest (0.812). Conclusion The incidence of CAPA was extremely high in patients admitted to the ICU. CAPA diagnosis mainly depends on microbiological evidence owing to non-specific clinical manifestations, routine laboratory examinations, and CT findings. The bronchoscopy should be performed and the BALF should be obtained as soon as possible. BALF GM are the most suitable microbiological examinations for the diagnosis of CAPA. Due to the timely and accuracy result of mNGS, it could assist in early diagnosis and might be an option in critically ill CAPA patients.